Implementasi Knowledge Management di Bimbingan Belajar - Tamara Putri Yadita; Aminuddin Irfani; Indra Fajar Alamsyah (Bandung Conference Series: Business and Management, 2024)
Abstract. This research focuses on understanding how Genza Education implements Knowledge Management, as well as its impact on increasing the capacity of human resources (HR). The purpose of this research is to explore the implementation of knowledge management at Genza Education Talaga Bestari tutoring center, as well as analyze the role of knowledge management in increasing human resource capacity at Genza Education Talaga Bestari tutoring center. The research method used is verification qualitative research with a case study. Data collection techniques include in-depth interviews, observation, and document studies. The data analysis techniques used are data reduction, data presentation, and conclusions. The results showed that the implementation of knowledge management at Genza Education is very important to create an environment that supports information exchange and collaboration. The implementation of Knowledge Management also helps Genza Talaga Bestari tutoring institution in overcoming rapid changes in curriculum, good teaching strategies, and structured knowledge storage. In addition, the application of Knowledge Management also provides the development of human resource competencies in the Genza Education Talaga Bestari tutoring institution. With Knowledge Management in place, the institution can ensure that the knowledge and skills acquired by tutors and other staff are well documented and accessible to all members of the organization and this also allows for efficient knowledge transfer, so that each tutor can utilize the existing knowledge to improve the quality of their teaching. Abstrak. Penelitian ini berfokus untuk memahami bagaimana Genza Education mengimplementasikan Knowledge Management, serta dampaknya pada peningkatan kapasitas sumber daya manusia (SDM). Tujuan penelitian ini adalah untuk mengeksplorasi implementasi knowledge management di bimbel Genza Talaga Bestari, serta menganalisis peran knowledge management dalam meningkatkan kapasitas sumber daya manusia di bimbingan belajar genza education talaga bestari. Metode penelitian yang digunakan adalah penelitian kualitatif verifikatif dengan case study. Teknik pengumpulan data meliputi wawancara mendalam, observasi, dan studi dokumen. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi knowledge management di Genza Education sangat penting untuk menciptakan lingkungan yang mendukung pertukaran informasi dan kolaborasi. Implementasi Knowledge Management juga membantu lembaga bimbingan belajar Genza Talaga Bestari dalam mengatasi perubahan cepat dalam kurikulum, strategi pengajaran yang baik, dan penyimpanan pengetahuan yang terstruktur. Selain itu, penerapan Knowledge Management juga memberikan pengembangan kompetensi sumber daya manusia yang ada di lembaga bimbingan belajar Genza Education Talaga Bestari. Dengan adanya Knowledge Management, lembaga dapat memastikan bahwa pengetahuan dan keterampilan yang diperoleh oleh para tutor dan staf lainnya didokumentasikan dengan baik dan dapat diakses oleh seluruh anggota organisasi dan ini juga memungkinkan terjadinya transfer pengetahuan yang efisien, sehingga setiap tutor dapat memanfaatkan pengetahuan yang ada untuk meningkatkan kualitas pengajaran mereka.